Variation in Perioperative Care across Centers for Infants Undergoing the Norwood Procedure - Pasquali, Sara K. (2012)
OBJECTIVES: In the Single Ventricle Reconstruction Trial, infants undergoing the Norwood procedure were randomized to a right ventricle-to-pulmonary-artery shunt or modified Blalock-Taussig shunt. Apart from shunt type, subjects received local standard of care. We evaluated variation in peri-operative care during the Norwood hospitalization across 14 trial sites. METHODS: Data on pre-operative, operative, and post-operative variables were collected prospectively on standardized case report forms, and variation across centers described for 546 enrolled subjects who underwent the Norwood procedure. RESULTS: Subjects' gestational age, birth weight, and proportion with hypoplastic left heart syndrome were similar across sites. In contrast, all recorded variables related to pre-operative care varied across centers, including fetal diagnosis (range 55–85%), preoperative intubation (range 29–91%), and enteral feeding. Perioperative/operative factors were also variable across sites including median total support time (range 74–189 minutes) and other perfusion variables, arch reconstruction technique, intraoperative medication use, and use of modified ultrafiltration (range 48–100%). Additional variation across centers was seen in variables related to postoperative care, including proportion with an open sternum (range 35–100%), median intensive care unit length of stay (range 9–44 days), type of feeding at discharge, and enrollment in a home monitoring program (range 1–100%; 5 sites did not have a program). Overall inhospital death/transplant occurred in 18% (range across sites 7–39%). CONCLUSIONS: Perioperative care during the Norwood hospitalization varies across centers. Further analysis evaluating the underlying causes and relationship of this variation to outcome is needed to inform future studies and quality improvement efforts.